A Political Decentralization under Khyber Pakhtunkhwa Local Government Act 2013: (A Case Study of Locally Elected Bodies in District Peshawar). - Khan, Shams (Journal of Peace, Development and Communication, 2023)
The basic objective of this study is to provide a detailed analysis of political decentralization under the Khyber Pakhtunkhwa Local Government Act of 2013. The local government system plays an important role in local development as well as in decision-making at the grass-roots level. Pakistan has practiced various forms of local government since its inception. However, such local government systems have not provided true know-how about political decentralization at the local level, either due to a lack of interest on the part of politicians or a lack of awareness on the part of the public. The present study has assessed the Local Government Act 2013 of KP in terms of political decentralization in the district of Peshawar. This research is based on quantitative and analytical approaches. The research work provides an answer to the main research question, which is how far political decentralisation has been implemented in District Peshawar. Regarding political decentralization the study argues that it has been implemented to a greater extent (67.7%) under the KP Local Government Act 2013. The scope of the study is confined to the district of Peshawar. Primary data has been analyzed with the help of descriptive and inferential statistics via SPSS software. Descriptive statistics include frequencies and percentages, while inferential statistics include the chi-square test and p-value.